Staging of esophageal and gastric cancer in 2014 - (:unkn) unknown (EDIZIONI MINERVA MEDICA, 2014)
Cancers of the upper gastrointestinal (GI) tract; esophageal and gastric carcinomas are highly lethal malignancies that have been ranked among the top 10 most frequent cancers and leading causes of cancer-related mortality. Universally, the tumor-node-metastasis (TNM) staging systems provided by the American Joint Committee on Cancer (AJCC) and the International Union Against Cancer (UICC) are used for esophageal and gastric cancers. Accurate locoregional staging has become critical for the application of appropriate stage-specific treatment options in the multimodality treatment era in order to achieve better patient outcomes. Endoscopic ultrasound (EUS) represents a valuable minimally invasive real-time imaging modality for the assessment of upper GI tract tumors providing evidence for tumor invasion depth and regional nodal involvement corresponding to the T and N status of the TNM staging system, but a clear understanding of its diagnostic performance, limits and complementary role to other imaging modalities is required. This review will focus on the literature about the role and value of EUS in the TNM staging of esophageal and gastric carcinoma. In addition:, an overview of the description of the current 7th editions of TNM staging and the revisions of the last editions compared to previous editions are presented.
Keywords: Esophageal carcinoma; Gastric carcinoma; Staging; Endoscopic ultrasound; POSITRON-EMISSION-TOMOGRAPHY; ENDOSCOPIC SUBMUCOSAL DISSECTION; SQUAMOUS-CELL CARCINOMA; FINE-NEEDLE ASPIRATION; LYMPH-NODE METASTASES; HIGH-GRADE DYSPLASIA; COMPUTED-TOMOGRAPHY; NEOADJUVANT CHEMOTHERAPY; ENDOSONOGRAPHIC ASSESSMENT; PROGNOSTIC-SIGNIFICANCE